Oscillation Damping Emulation Using Superconducting Magnetic Energy Storage based on Sine Cosine Algorithm on Jawa Indonesian Power Grid - Abdillah M.; Setiadi H.; Manuaba I.B.G.; Farid I.W.; Ramasamy A.K.; Verayiah R.; Marsadek M.B. (Intelligent Network and Systems Society, 2023)
This paper proposed method for emulated oscillation damping using superconducting magnetic energy storage (SMES) devices. To find the best oscillation damping emulation the parameter of SMES is optimized using sine cosine algorithm (SCA). Jawa Indonesia power grid is used as the test system to observe the efficacy of the proposed controller method. Time domain simulation is carried out to investigate how the proposed method can be used to emulate the oscillation damping in the system. From the simulation results, it is noticeable that SMES based on SCA could be used to emulate the oscillation damping on the Jawa Indonesian power grid. This is indicated by the small overshoot and fast settling time of rotor speed dynamics response (Overshoot and settling time of Suralaya power plant -0.000448 and 5.51 second) 2022, International Journal of Intelligent Engineering and Systems.All Rights Reserved.